The Attitudes of Ankara University Researchers towards Research Data Management and Barriers to Data Sharing - Zencir, Mithat Baver; Oğuz, Tülay (Information World, 2020)
Research data has a key importance for the science world, for their verification use, economic and social values. Therefore, the data must be made open and the barriers to sharing must be removed. This study aims to reveal the attitudes of researchers -who managed Scientific Research Projects within Ankara University- towards research data management and describe barriers to data sharing. Descriptive method was used in the study and survey technique was preferred for data collection. Data collected from 194 researchers revealed that researchers were not able to manage data effectively. Most of the researchers do not prepare a written data management plan, or they do not plan applications related to data after the completion of the research, and they retain large amounts of data outside the institutional storage areas as well as not using accepted standards in creating metadata. In this study, the effect of scientific fields on data management process has also been revealed, and findings demonstrated that there are significant differences among scientific fields in terms of types of data created, types of data files, amount of data produced, familiarity with metadata and reasons affecting data sharing. One of the most important results revealed in this study is that participants find it sufficient to share data only through publication. Therefore, researchers prefer to share their results/findings, not research data. This contradicts the idea of open research data. Barriers to researchers’ data sharing are closely related to the current academic system and the anxiety of stealing and research ideas/methods. In addition, issues such as problems in data management processes, legal regulations and service deficiencies are other barriers to data sharing.